In vitro antiplasmodial activity and toxicological profile of extracts, fractions and chemical constituents of leaves and stem bark from Dacryodes edulis (Burseraceae) - Kevine Johane Jumeta Dongmo; Mariscal Brice Tchatat Tali; Yannick Stéphane Fotsing Fongang; Pierre Leonel K. Tafokeu Taguimjeu; Donald Ulrich Kenou Kagho; Gabin Thierry Bitchagno; Bruno Ndjakou Lenta; Fabrice Fekam Boyom; Norbert Sewald; Silvère Augustin Ngouela (BMC, 2023)
Abstract Background Dacryodes edulis is a plant that belongs to the Burseraceae family. It is widely used traditionally alone or in association with other plants in Cameroonian folk medicine to cure wounds, fever, headaches, and malaria. The aim of this work was to investigate the leaves and stem bark of D. edulis with an emphasis on the antiplasmodial and cytotoxic effects of extracts, fractions, and isolated compounds. Methods Extracts, fractions, and some isolated compounds were subjected to antiplasmodial activity screening in vitro against chloroquine-sensitive 3D7 and multidrug resistant Dd2 strains of Plasmodium falciparum using a SyBr Green fluorescence-based assay. The cytotoxicity of active extracts, fractions, and compounds was tested against mammalian Raw cell lines using an in vitro resazurin-based viability assay. The structures of the compounds were determined based on their NMR and MS data. The in vivo toxicity using female BALB/c mice was performed on the most active extract according to the protocol of OECD (2002), guideline 423. Results The hydroethanolic extract from the leaves of D. edulis displayed good antiplasmodial activity with IC50 values of 3.10 and 3.56 μg/mL respectively on sensitive (3D7) and multiresistant (Dd2) strains of P. falciparum. Of the sixteen compounds isolated, 3,3',4-tri-O-methylellagic acid (4) exhibited the highest antiplasmodial activity against PfDd2 strains with an IC50 value of 0.63 μg/mL. All extracts, fractions, and isolated compounds demonstrated no cytotoxicity against Raw cell lines with CC50 > 250 μg/mL. In addition, the most active extract on both strains of P. falciparum was nontoxic in vivo, with a LD50 greater than 2000 and 5000 mg/kg. A phytochemical investigation of the stem bark and leaves of D. edulis afforded sixteen compounds, including two xanthones (1-2), three ellagic acid derivatives (3-5), one phenolic compound (6), one depside (7), one triglyceride (8), one auranthiamide acetate (9), one gallic acid derivative (10), four triterpenoids (11-14), and two steroids (15-16). Compounds 1, 2, 5, 7, 8, and 9 were herein reported for the first time from the Burseraceae family. Conclusion This work highlights the good in vitro antiplasmodial potency of the hydroethanolic extract of the leaves of this plant and that of two isolated constituents (3,3',4-tri-O-methylellagic acid and ethylgallate) from the plant. These biological results support the use of D. edulis in traditional medicine against malaria.